SISTEM PEMANTAUAN ONLINE (ONLIMO) KUALITAS AIR DENGAN MENGGUNAKAN SISTEM KOMUNIKASI GSM - Wahyono, Heru Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Nowadays the water quality monitoring project that had been doing bygovernment institution is increase due to decreasing of water quality. Manymethods and techniques are developed for water quality monitoring. Thecommunication technology development such as GSM/CDMA technologycan be used as new network infrastructure for water quality monitoring.People over the world are now using this technology as newcommunication medium. With SMS as the one of services from GSMtechnology people can send or receive messages easily. By using theintegration of digital sensor for water quality, digital data logger and GSMmodem as communication unit, the water quality can be monitored ascheap as sending the SMS by phone cell. The critical value of water qualityparameter also can be monitored and sent to the phone cell of decisionmaker.